2021
DOI: 10.3390/biom11010082
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Mesenchymal Stem/Stromal Cell Therapy for Inflammatory Bowel Diseases: An Up-to-Date Systematic Review

Abstract: Inflammatory bowel disease (IBD) is a chronic inflammatory disorder of the gut that can lead to severe gastrointestinal symptoms, malnutrition, and complications such as fistulas and cancer. Mesenchymal stem/stromal cells (MSCs) are being investigated as a novel therapy for IBD and have been demonstrated to be safe and effective for perianal fistulizing Crohn’s disease (PFCD). This systematic review aims to present the most recent studies on the safety and efficacy of MSC therapy in IBD. A detailed search stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 55 publications
1
45
0
1
Order By: Relevance
“…The cells sprinted into the clinic stage center due to their features of versatile development potential, self-renewal, allogenic compatibility, and immunomodulatory effects. MSCs are currently being widely tested as a cellular therapy in chronic intestinal diseases, including IBD, and showed promising clinical outcomes with unmet optimization and improvement [28][29][30], such as in vivo low level of MSC recruitment, and persistence decreased their therapeutic efficacy [31].…”
Section: Discussionmentioning
confidence: 99%
“…The cells sprinted into the clinic stage center due to their features of versatile development potential, self-renewal, allogenic compatibility, and immunomodulatory effects. MSCs are currently being widely tested as a cellular therapy in chronic intestinal diseases, including IBD, and showed promising clinical outcomes with unmet optimization and improvement [28][29][30], such as in vivo low level of MSC recruitment, and persistence decreased their therapeutic efficacy [31].…”
Section: Discussionmentioning
confidence: 99%
“…The author observed BM-MSCs treatment decelerated the loss of renal allograft function [ 27 ]. The systematic review about MSC therapy with 32 studies for Inflammatory Bowel Diseases (IBD) revealed that MSCs are proving to be a very exciting addition to the limited therapies available for IBD [ 28 ]. A systematic review about HSC transplantation in SLE with 15 studies revealed that most of the studies showed remission in the majority of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Such as stem cell transplantation results in satisfactory clinical response in SLE patients; MS patients and IBD et al. [ 21 , 28 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Significant numbers of other clinical trials are dealing with the use of MSCs' immunomodulatory properties as standalone therapy for various diseases and conditions associated with overactivated immune systems. MSCs were tested for treatment of rheumatoid arthritis and osteoarthritis [225], multiple sclerosis [226], inflammatory bowel disease [227], systemic lupus erythematosus [228], diabetes mellitus [229], among other pathologies. In most reported cases, good safety profiles and encouraging outcomes were reported.…”
Section: Translation To the Clinicmentioning
confidence: 99%